2007
DOI: 10.1002/ptr.2066
|View full text |Cite
|
Sign up to set email alerts
|

Novel antitumor activities of Kushen flavonoids In Vitro and In Vivo

Abstract: Kushen (KS), the dried roots of Sophora flavescens Aiton, has a long history of use in traditional Chinese medicine to treat inflammatory diseases and cancer. Kushen alkaloids (KS-As) and Kushen flavonoids (KS-Fs) are the well characterized components in KS. KS-As have been considered biologically active and developed in China as anticancer drugs. In an effort to screen novel antitumor agents from botanicals, more potent antitumor activities were identified in KS-Fs than in KS-As. KS-Fs were able to inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Thus, the structure of 3 was established and named as flavesine C. Thus, compound 4 was identified and named as flavesine D. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 at C-13′ and C-14′, as well as the presence of methylene (δ C 20.3) and methine (δ C 45. 6) carbons. These differences suggested that the double bond was reduced in 5, which was confirmed by the 1 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 In addition, the other two known compounds were identified as matrine …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the structure of 3 was established and named as flavesine C. Thus, compound 4 was identified and named as flavesine D. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 at C-13′ and C-14′, as well as the presence of methylene (δ C 20.3) and methine (δ C 45. 6) carbons. These differences suggested that the double bond was reduced in 5, which was confirmed by the 1 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 In addition, the other two known compounds were identified as matrine …”
Section: Resultsmentioning
confidence: 99%
“…1,2 The modern pharmacological studies showed that the extracts of S. flavescens displayed the anti-virus, anti-fungi, anti-inflammation, and anti-tumor effects. [3][4][5][6] Phytochemical investigations suggested that matrine-type alkaloids and flavonoids were the main components of this plant. [7][8][9][10][11][12][13][14][15] More than forty matrine-type alkaloids had been isolated from Sophora plants since 1895.…”
Section: Introductionmentioning
confidence: 99%
“…Taxol was used as a standard in the cytotoxic assay (Wani & Horwitz 2014) and its IC 50 value is 0.20 mM. Compound 1 and 2 exhibited moderate cytotoxicity against human ECA-109 (Sun et al 2007) compared with report and gave IC 50 values of 23.22 and 26.76 mM, respectively.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Thus, it is important to develop new angiogenic inhibitors that target tumor VM or to combine anti-VM drugs with conventional chemotherapies. Traditional Chinese medicines are reported to have multifunctional antitumor activities (10). …”
Section: Introductionmentioning
confidence: 99%